OBTAINING A COMPOSITION OF OIL LUBRICANT, NANOPOWDER OF ALUMINUM OXIDE AND SURFACE-ACTIVE AGENT FOR REDUCTION OF FRICTION IN ROLLING BEARINGS - Kustov, O.Yu. (Perm Federal Research Centre Journal, 2015)
Research has been conducted on ultradispersed powder of aluminum oxide with + modification of crystal lattice produced by "Plazmoterm" company, Moscow. Experiments on breaking up conglomerates were performed by vibration stand and desk ultrasonic dispergator, which was found the most effective at higher frequencies and high power at long period.To prevent adhesion of powder particles the oleic acid, which is pronounced surface-active agent (SAA), was used. By ultrasonic dispersing powder with oleic acid, the suspension with particles size of 20-80 nm was obtained, which does not precipitate in oil.